Effects of perfusion on diffusion changes in human brain tumors. Issue 4 (6th February 2013) - Cohen, Alexander D.; LaViolette, Peter S.; Prah, Melissa; Connelly, Jennifer; Malkin, Mark G.; Rand, Scott D.; Mueller, Wade M.; Schmainda, Kathleen M.
Abstract : Purpose: To characterize the influence of perfusion on the measurement of diffusion changes over time when ADC is computed using standard two‐point methods. Materials and Methods: Functional diffusion maps (FDMs), which depict changes in diffusion over time, were compared with rCBV changes in patients with brain tumors. The FDMs were created by coregistering and subtracting ADC maps from two time points and categorizing voxels where ADC significantly increased (iADC), decreased (dADC), or did not change (ncADC). Traditional FDMs (tFDMs) were computed using b = 0, 1000 s/mm 2 . Flow‐compensated FDMs (fcFDMs) were calculated using b = 500, 1000 s/mm 2 . Perfusion's influence on FDMs was determined by evaluating changes in rCBV in areas where the ADC change significantly differed between the two FDMs. Results: The mean ΔrCBV in voxels that changed from iADC (dADC) on the tFDM to ncADC on the fcFDM was significantly greater (less) than zero. In addition, mean ΔrCBV in iADC (dADC) voxels on the tFDM was significantly higher (lower) than in iADC (dADC) voxels on the fcFDM. Conclusion: The ability to accurately identify changes in diffusion on traditional FDMs is confounded in areas where perfusion and diffusion changes are colocalized. Flow‐compensated FDMs, which use only non‐zero b‐values, should therefore be the standard approach. J. Magn. Reson. Imaging 2013;38:868–875. © 2013 Wiley Periodicals, Inc.